The causes and consequences of takeover defense: Evidence from greenmail - Bhagat, Sanjai; Jefferis, Richard H. (Journal of Corporate Finance, 1994)
We study the joint distribution of ownership, performance, managerial turnover, and takeover activity at repurchasing firms during a five-year period centered on the repurchase, and compare this to the distribution of these variables for a control sample selected on the basis of size and industry. This evidence illuminates the link between defensive activity and performance, as well as the impact of defensive activity on the experience of firms and managers. We find that the performance of firms that pay greenmail is no worse than the performance of firms of similar size that operate in the same industry, either prior to the repurchase or following the repurchase. The fate of managers at firms that pay greenmail appears to reflect their performance, as does the occurence of takeover activity. The frequency of takeover activity cannot be distinguished from the frequency of takeover activity at firms involved in a 13-D filing. Bid premia appear to be unaffected by the payment of greenmail.